Silver Nanoparticles Stabilised by Cationic Gemini Surfactants with Variable Spacer Length - Pisárčik, Martin; Jampílek, Josef; Lukáč, Miloš; Horáková, Renáta; Devínsky, Ferdinand; Bukovský, Marián; Kalina, Michal; Tkacz, Jakub; Opravil, Tomáš (Molecules (Basel, Switzerland), 2017)
The present study is focused on the synthesis and investigation of the physicochemical and biological properties of silver nanoparticles stabilized with a series of cationic gemini surfactants having a polymethylene spacer of variable length. UV-VIS spectroscopy, dynamic light scattering, scanning electron microscopy and zeta potential measurements were applied to provide physicochemical characterization of the silver nanoparticles. The mean size values of the nanoparticles were found to be in the 50 to 115 nm range. From the nanoparticle size distributions and scanning electron microscopy images it results that a population of small nanoparticles with the size of several nanometers was confirmed if the nanoparticles were stabilized with gemini molecules with either a short methylene spacer (two or four -CH₂- groups) or a long spacer (12 -CH₂- groups). The average zeta potential value for silver nanoparticles stabilized with gemini molecules is roughly independent of gemini surfactant spacer length and is approx. +58 mV. An interaction model between silver nanoparticles and gemini molecules which reflects the gained experimental data, is suggested. Microbicidal activity determinations revealed that the silver nanoparticles stabilized with gemini surfactants are more efficient against Gram-negative bacteria and yeasts, which has a direct relation to the interaction mechanism of nanoparticles with the bacterial cell membrane and its structural composition.
Keywords: Fungi; micely; Silver; silver nanoparticle; houby; Gram-Negative Bacteria; nanoparticle stability; Surface-Active Agents; microbicidal activity; Anti-Infective Agents; kovové nanočástice; gemini surfactant; Metal Nanoparticles; Micelles; povrchově aktivní látky; surfactant spacer; gramnegativní bakterie; stříbro; antiinfekční látky